Transnational banks and the external indebtedness of developing countries: impact of regulatory changes - Bouchet, Michel H. (UN New YorkUS, 1992)
Reviews the modifications introduced in several creditor countries and examines their implications for the incentives of transnational banks to participate in debt-reduction efforts and/or grant of new loans as a means to provide cash-flow relief. Points out some areas for improvements in regulatory frameworks in the context of discussion of adjustments in each creditor country. Suggests some general areas for further reforms.